A Methodological Review of Fashion Marketing Studies - ÖZTAY, Hilal (Girisimcilik Inovasyon ve Pazarlama Arastirmalari Dergisi, 2021)
In this study, fashion marketing studies were examined in terms of method in line with the paradigms adopted in the social sciences. Firstly, explanations of the concepts were presented in order to make sense of the nature of positivist, post-positivist paradigms and quantitative, qualitative research. Then, theses written in the field of fashion marketing in The Council of Higher Education (CoHE) National Thesis Center were analyzed by content analysis. These analyzes were carried out to show the distribution of theses by years in terms of paradigm. In addition, the data collection tools, data analysis techniques and research patterns utilized in the studies were examined, and the techniques that were widely adopted and started to be adopted were explained. According to the findings, quantitative studies are widely used in fashion marketing studies and it has been observed that the use of qualitative and mixed studies have increased in recent years. In quantitative studies, questionnaires and statistical analyzes are widely used and causal research is often applied. In qualitative studies, different data collection and analysis methods are adopted in accordance with the characteristics and design of the research. It has been concluded that mixed studies are mostly designed by adopting multiple methods in accordance with the purpose.
Keywords: 4. Education